Pengaruh lokasi, harga, dan keberagaman produk terhadap kepuasan konsumen Alfamart Situsari - Muhamad Yusuf Fahrezi; Nika Sintesa (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
This study aims to analyze the influence of location, price, and product diversity on consumer satisfaction at Alfamart Situsari. The research method used is quantitative with a survey approach through the distribution of questionnaires to 210 respondents who have shopped at Alfamart Situsari. The sampling technique used was simple random sampling, while data analysis was conducted using Partial Least Squares (PLS) with the SmartPLS 3.2.9 software. The results of the study indicate that, individually, the variables of location, price, and product variety significantly influence customer satisfaction. Simultaneously, these three variables were also found to have a significant influence on consumer satisfaction. This finding indicates that the more strategic the location, the more competitive the price, and the more diverse the products offered, the higher the level of consumer satisfaction will be. This study contributes theoretically to strengthening research on consumer satisfaction in the modern retail sector and provides practical benefits for Alfamart management in formulating more effective marketing strategies. By improving aspects of location, price, and product diversity, Alfamart can maintain customer loyalty while enhancing its competitiveness in the competitive retail market.